The Regional Analysis on the Relationship of Income and Economic Growth on the Savings of Filipino Households over the Business Cycles - Jose Alberto Bacud; Yna Bless Nieto; Atheana Zui Patungan; Peter Jeff Camaro (UJoST- Universal Journal of Science and Technology, 2023)
This study analyzes the relationship of income and economic growth toward the savings of Filipino households over the business cycles. Savings has been studied to have various determinants. Thus, the researchers of this study were urged to provide empirical evidence in this topic within the economic context of the Philippines. The study would like to establish the conventional income-savings relationship and prove the causal relationship of economic growth to savings, both of which will be observed through a business cycle to understand the behavior of saving better. The researchers used Panel Data Regression analysis to find the significant predictors among the variables. It was found that the highest income range positively affects savings, and interest rates negatively affect it. Moreover, CAR was proven to have the highest average savings among other regions in the Philippines. However, it is only averaged compared to ARMM regarding Regional GDP. With this, the study provides policymakers with a better outlook on what factors they should focus on to boost savings and consequently improve investment and further economic growth.